(untitled) (Research, Society and Development, 2022)
The research discusses the behavior of studies on female entrepreneurship and agriculture. The objective is to analyze the profile of scientific publications related to female entrepreneurship and agriculture in the period 2000 to 2021 with a view to identifying opportunities for future research through systematic literature review. In this time frame, 111 publications were analyzed, where the research approaches were closely aligned with the socioeconomic contributions of women entrepreneurs to more sustainable development. The results showed that studies on female entrepreneurship address five main categories: a) Gender diversity; b) Technology and social networks; c) Institutional entrepreneurship; d) Behavior analysis; e) Female entrepreneurial capacity and strategy. The main researches carried out were of a qualitative nature, making use mainly of obtaining primary data to understand the result in depth. Therefore, as a suggestion for future research, the importance of carrying out further research is highlighted, aimed at evaluating methodologies for use in public policies focused on the theme and bringing female entrepreneurship in both rural and urban agriculture to the academic scene.